Effective Biodegradation of Mycotoxin Patulin by Porcine Pancreatic Lipase - Liu, Bingjie; Peng, Xiaoning; Meng, Xianghong (Frontiers in Microbiology, 2018)
Patulin is a common contaminant in fruits and vegetables, which is difficult to remove. In this study, the biodegradation of patulin using porcine pancreatic lipase (PPL) was investigated. The method of HPLC was used to analyze the concentration of patulin. Batch degradation experiments were performed to illustrate the effect of PPL amount, pH, temperature, contact time, and initial concentration. Besides, the degradation product of patulin was characterized by full wavelength scanning and MS technologies. The results showed that the optimum degradation conditions of PPL for patulin was observed at pH 7.5, 40°C for 48 h. The percentage of degradation could reach above 90%. The structure of degradable product of patulin was inferred by the molecular weight 159.0594, named C7H11O4+. It indicated that PPL was effective for the degradation of patulin in fruits and vegetables juice.